2015
DOI: 10.4049/jimmunol.1501220
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirements of TCR Signaling in Homeostatic Maintenance and Function of Dendritic Epidermal T Cells

Abstract: Dendritic Epidermal T Cells (DETCs) are generated exclusively in the fetal thymus and maintained in the skin epithelium throughout postnatal life of the mouse. DETCs have restricted antigenic specificity due to their exclusive usage of a canonical TCR. Although the importance of the TCR in DETC development has been well established, the exact role of TCR signaling in DETC homeostasis and function remains incompletely defined. Here, we investigated TCR signaling in fully matured DETCs by lineage-restricted dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 52 publications
0
66
0
Order By: Relevance
“…Nevertheless, because some of the effects observed after 2-DG treatment could be mediated by other cells than γδ IELs involved in the response to enteric infection (Chieppa et al, 2006), we decided to directly address the role of infection-induced glycolysis in γδ IELs. To that end, we interbred tamoxifen-inducible Tcrd CreER (Zhang et al, 2015) with mice carrying loxp -flanked alleles of the Slc2a1 gene encoding one of the main glucose transporters in T cells, Glut1 (Buck et al, 2015). EFA analysis on γδ IELs isolated from tamoxifen-treated, Salmonella -infected iTCRγδ × Slc2a1 f/+ (iTCRγδ ΔGlut1) mice demonstrated that removal of one Slc2a1 allele was sufficient to prevent infection-induced metabolic responses in γδ IELs, both in terms of ECAR and OCR upregulation (Figure 5B, G).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, because some of the effects observed after 2-DG treatment could be mediated by other cells than γδ IELs involved in the response to enteric infection (Chieppa et al, 2006), we decided to directly address the role of infection-induced glycolysis in γδ IELs. To that end, we interbred tamoxifen-inducible Tcrd CreER (Zhang et al, 2015) with mice carrying loxp -flanked alleles of the Slc2a1 gene encoding one of the main glucose transporters in T cells, Glut1 (Buck et al, 2015). EFA analysis on γδ IELs isolated from tamoxifen-treated, Salmonella -infected iTCRγδ × Slc2a1 f/+ (iTCRγδ ΔGlut1) mice demonstrated that removal of one Slc2a1 allele was sufficient to prevent infection-induced metabolic responses in γδ IELs, both in terms of ECAR and OCR upregulation (Figure 5B, G).…”
Section: Resultsmentioning
confidence: 99%
“…To do this, we injected mice bearing Tcrd CreER and Rosa26 fl-STOP-fl-ZsGreen alleles (Zhang et al, 2015) with tamoxifen to label DN thymocytes, which express Tcrd , and we tracked Tcra rearrangements in those cells over time as they entered into and matured in the DP compartment. A single dose of tamoxifen preferentially labeled DN2 and DN4-CD8 ISP thymocytes, which progressively moved into the DN3 and DP compartments, respectively, over 72 hrs (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Tcrd CreER × Rosa26 fl-STOP-fl-zsGreen mice (Zhang et al, 2015), mice homozygous for the HYα allele (Buch et al, 2002; Hawwari and Krangel, 2007), and mice homozygous for the INT1-2 deletion (Chen et al, 2015), were all of a mixed 129 and C57/BL6 genetic origin, and were previously described. HYα mice were bred with Rag2 −/− mice to generate Rag2 −/− mice either homozygous or heterozygous for the HYα allele (Shinkai, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…1A) (9). The Tcrd gene is actively transcribed in all developing T cells (10) and subsequently deleted on completion of TCRα gene rearrangement during the transition from the double positive (DP) stage to the single positive (SP) stage during thymopoiesis (11).…”
Section: Resultsmentioning
confidence: 99%